Probiotics restore impaired spatial cognition and synaptic plasticity of prenatally-stressed male rats: focus on hippocampal and intestinal tight junctions - Fatemeh Aghighi Bidgoli; Sayyed Alireza Talaei; Abolfazl Azami Tameh; Mahmoud Salami (Neurobiology of Stress)
Bidirectional communication between the gut microbiota and the nervous system founded the gut-microbiota-brain axis, substantially affects numerous vital functions of the body. Stress, as the body's natural reaction to stressful situations, in turn, affects the functioning of various organs. Through evaluating long-term potentiation (LTP) and spatial memory assessment using the Morris water maze, we aimed to examine the effect of prenatal stress on the electrophysiological and behavioral aspects of hippocampus-dependent spatial memory. The relationship of the synaptic plasticity and learning and memory with the hypothalamus-pituitary-adrenal (HPA) axis and the integrity of blood-brain and intestinal barriers were also examined. The experimental subjects were introduced to probiotic treatment to assess how the supplementation influences stress-related alterations. The prenatal stress effectively impaired both LTP occurrence and behavioral function. It also led to disruption of blood-brain and gut barriers and increased serum level of corticosterone. The probiotic supplementation positively affected the synaptic plasticity and learning and memory. It also improved the integrity of both barriers and reduced the stress hormone corticosterone. Whereas there is a reverse relationship between stress and the hippocampus-dependent spatial memory, normal stress hormone, and the integrity of intestinal and brain barriers, the probiotic supplements improve all impairments. We conclude that the HPA axis plus the blood-brain and intestinal barriers play a role in hippocampus-dependent spatial memory that are substantially affected by the beneficial gut and probiotic bacteria.